Wander in the dark - Emill, Jumata (New York : Delacorte Press, 2024)
Two brothers must come together to solve the murder of the most popular girl in school after one of them is caught fleeing the scene of her death.
Ages 14+
Keywords: African Americans -- Juvenile fiction; Brothers -- Juvenile fiction; Estranged families -- Juvenile fiction; Murder -- Juvenile fiction; Secrecy -- Juvenile fiction; Murder -- Fiction; Brothers -- Fiction; Family problems -- Fiction; African Americans -- Fiction; Mystery and detective stories; New Orleans (La.) -- Juvenile fiction; New Orleans (La.) -- Fiction; Detective and mystery stories; JUVENILE FICTION -- General; Detective and mystery fiction; Thrillers (Fiction); Detective and mystery fiction; Thrillers (Fiction); Novels